School Principal's Management Strategies on the Productivity of Teachers - Firmina, Firmina; Wicaksono, Luhur; Radiana, Usman; Junanto, Tulus (JUPE : Jurnal Pendidikan Mandala, 2024)
Princlipal plannling clan hellp telachers imlprove thleir albility tlo clarry olut learlning. Contlrol ils a prolcess iln mealsuring perflormance anld tlhe acltions talken alre enslured tlo ble succlessful slo als tlo achlieve tlhe stalted golals. This research uses a qualitative approach which aims to understand a phenomenon in a natural social context by prioritizing the process of in-depth communication interaction between the researcher and the phenomenon being studied. To find out the development strategy method, namely by analyzing external factors in the form of opportunities and threats as well as internal factors in the form of strengths and weaknesses by using SWOT analysis. From the results of the research, it shows that in realizing managerial strategies, there are processes that need tlo ble impllemented tlo incrlease tealcher wolrk prodluctivity bly melans olf strlategy formlulation, straltegy implelmentation alnd strlategy evalluation. Iln thle conltrol aslpect, ilt ils carrlied olut throlugh a suplervisory prolcess throulgh superlvision actlivities, anld gilving punilshlment. Tllhe schllool prinlcilpal alls alln admilnlistrator ills resplolnsible fllor thle smoolth rulnning olf edulcation alnd tealching lin hlis schlool, als welll als a desilgner olf managlerial stratlegies invollving parlties inclulding teaclhers, superlvisors, foundlations alnld colmlmittees. In the process that will be carried out by the school principal consists of, strategy formulation which includes vilsion, mislsion, golals, stratlegies anld polilcies olf thle schlool prilncipal iln incrleasing telacher wolrk prodluctivity, thlen impllementing stratelgies consistling olf progrlams, budglets alnd procledures. Anld finallly evalluation anld colntrol, iln whlich calse lit ils imporltant lto slee whetlher tlhe planlned proglram achielves ilts gloals olr nlot. Keywords: Planlning, Conltrol, Teacher Work ProductivityPrinclipal plannling clan hellp telachers imlprove thleir albility tlo clarry olut learlning. Contlrol ils a prolcess iln mealsuring perflormance anld tlhe acltions talken alre enslured tlo ble succlessful slo als tlo achlieve tlhe stalted golals. This research uses a qualitative approach which aims to understand a phenomenon in a natural social context by prioritizing the process of in-depth communication interaction between the researcher and the phenomenon being studied. To find out the development strategy method, namely by analyzing external factors in the form of opportunities and threats as well as internal factors in the form of strengths and weaknesses by using SWOT analysis. From the results of the research, it shows that in realizing managerial strategies, there are processes that need tlo ble impllemented tlo incrlease tealcher wolrk prodluctivity bly melans olf strlategy formlulation, straltegy implelmentation alnd strlategy evalluation. Iln thle conltrol aslpect, ilt ils carrlied olut throlugh a suplervisory prolcess throulgh superlvision actlivities, anld gilving punilshlment. Tllhe schllool prinlcilpal alls alln admilnlistrator ills resplolnsible fllor thle smoolth rulnning olf edulcation alnd tealching lin hlis schlool, als welll als a desilgner olf managlerial stratlegies invollving parlties inclulding teaclhers, superlvisors, foundlations alnld colmlmittees. In the process that will be carried out by the school principal consists of, strategy formulation which includes vilsion, mislsion, golals, stratlegies anld polilcies olf thle schlool prilncipal iln incrleasing telacher wolrk prodluctivity, thlen impllementing stratelgies consistling olf progrlams, budglets alnd procledures. Anld finallly evalluation anld colntrol, iln whlich calse lit ils imporltant lto slee whetlher tlhe planlned proglram achielves ilts gloals olr nlot.